The role of landscape management practices to address natural resource degradation and human vulnerability in Awash River Basin, Ethiopia - Mekuria, Wolde; Tadesse, Mulugeta; Admassu, W.; Asmame, B.; Tessema, A.; Abebe, S.; Shibiru, E.; Yirga, M.; Jorgi, Y.; Abdu, F.; Belay, B.; Seid, J.; et al. (Elsevier, 2023)
Landscape management practices (LMP) support addressing the vulnerability of small-scale producers (SSPs) through providing a means of sustaining and strengthening community livelihoods and building their resilience and the environment. However, addressing the vulnerability of SSPs through the implementation of LMP requires meaningful community engagement and assessing the benefits and costs from the perspective of local communities. This study was conducted in two watersheds, Maybar-Felana and Gelana, in the Awash River basin, Ethiopia. The study assessed the links between natural resource degradation and the vulnerability of SSPs, local communities' opinion on the benefits and costs of LMP and the implications of implementing LMP for addressing vulnerability. It gathered and analyzed data through key informant interviews (KII), focus group discussions (FGDs) and GIS and remote sensing techniques. Diverse LMP such as afforestation/reforestation, exclosures, terrace and bunds and crop- and soil-based soil amendments were adopted in the studied watersheds. These practices contributed to the improvement of natural resources such as forests and the services they provide. Over the last 21 years (2000− 2021), forest cover increased by 11.5 and 42.5% in Maybar-Felana and Gelana watersheds, respectively, while shrublands increased by 41.1% in Maybar-Felana. In line with this, the SSPs identified multiple benefits of LMP including the restoration of degraded vegetation, reducing runoff and soil loss, improving access to water for multiple uses and increasing agricultural productivity. The adopted LMP contributed to reducing livelihood vulnerability through reducing incidents of weather extremes such as flood and drought, improving food and water security, enhancing resource availability, and building livelihood assets. The SSPs also identified multiple economic and social costs of LMP, suggesting that addressing the economic and social costs through balancing short-term economic losses with long-term environmental benefits of interventions is crucial to sustaining the LMP and the benefits they provide.